THE PROBLEM OF MEANING SELECTION IN TRANSLATION STUDIES: ON THE EXAMPLE OF MULTIPLE MEANINGFUL WORDS ("Conference on Universal Science Research 2023", 2025)
This article analyzes the problem of meaning selection, one of the most complex issues in translation studies, on the example of multi-meaning words (polysemantic units). The phenomenon of polysemanticity is a natural feature of languages, which creates problems of semantic ambiguity and equivalence in the translation process. The article highlights the role of context, pragmatic factors, and cultural factors in meaning selection